2020
DOI: 10.1039/c9ra09873a
|View full text |Cite
|
Sign up to set email alerts
|

Gram-scale synthesis of ultra-fine Cu2O for highly efficient ozone decomposition

Abstract: Dozens of grams of ultra-fine Cu2O with efficient ozone decomposition was prepared by a facile liquid phase reduction method at room temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 55 publications
(62 reference statements)
0
4
0
Order By: Relevance
“…According to the BET characterization results, Cu 2 S-P has the largest specific surface area and the smallest average pore size of about 5 nm. Although studies [33,34] have shown that specific surface area is not a decisive indicator of the performance of ozone catalysts, Cu 2 S-P has a larger specific surface area and pore capacity compared to other structures, which can improve its contact efficiency with ozone gas flow and is a favorable factor in situations where surface chemical properties are similar. Although the sample with the best performance also has the largest specific surface area, overall, the difference in specific surface area among the three morphologies of Cu 2 S particles is not significant.…”
Section: Resultsmentioning
confidence: 99%
“…According to the BET characterization results, Cu 2 S-P has the largest specific surface area and the smallest average pore size of about 5 nm. Although studies [33,34] have shown that specific surface area is not a decisive indicator of the performance of ozone catalysts, Cu 2 S-P has a larger specific surface area and pore capacity compared to other structures, which can improve its contact efficiency with ozone gas flow and is a favorable factor in situations where surface chemical properties are similar. Although the sample with the best performance also has the largest specific surface area, overall, the difference in specific surface area among the three morphologies of Cu 2 S particles is not significant.…”
Section: Resultsmentioning
confidence: 99%
“…45 It should be noted that it is difficult to accurately distinguish the oxidation state of copper by the location of XPS spectra due to the close binding energy of Cu + and Cu 2+ states. 22,46 Therefore, copper in 0.5CeO 2 /0.25CuO/3DOM SiO 2 may have both ions.…”
Section: Surface Xps Analysismentioning
confidence: 99%
“…Although noble metal catalysts such as Pt, Pd, Au, and Ag have demonstrated excellent performance for catalyzing ozone decomposition, their high cost discourages their wide application. Therefore, the transition metal oxide catalysts were mainly developed due to their lower prices, larger reserves, and good activity. In particular, manganese oxide catalysts shown excellent activity in removing ozone under mild conditions and have been extensively reported and modified to improve their performance, such as Ce-OMS-2, H-MnO 2 , Li-K-OMS-2, and MnO 2 @GR . Nonetheless, manganese-based catalysts still have the problem that oxygen-containing species (e.g., O 2 – , O 2 2– , and H 2 O) occupy the active site (oxygen vacancy) and lead to catalyst deactivation. Recently, some layered double hydroxides (LDHs) and layered double oxides derived from LDH were developed to eliminate ozone, and especially, the NiFe-LDH catalyst exhibited outstanding performance and promising application potential for removing ozone.…”
Section: Introductionmentioning
confidence: 99%